Self-assessment impact on EFL learners’ speaking fluency and accuracy: Does level of proficiency matter? - Goodarz Alibakhshi; Abdullah Sarani (Teaching English Language, 2014)
Since the 1970s, self-assessment in education has gained increasing currency and has been studied in a considerable number of quantitative studies. In line with this theoretical and experimental background, this study aimed at investigating the effect of self-assessment on intermediate and upper-intermediate language learners’ speaking fluency and accuracy in Iran. Thirty pre-intermediate and thirty upper-intermediate students participated in the study in a pretest-posttest control/experimental group design. The data were analyzed through ANCOVA test. The results indicated that self-assessment positively affected participants’ speaking accuracy and fluency. Also, self-assessment had a greater effect on upper-intermediate learners than pre-intermediate ones. Moreover, speaking fluency benefitted more from self-assessment than speaking accuracy did. The findings can be applied by both EFL learners and teachers.